Peran Dinas Sosial Dalam Peningkatan Kesejahteraan Lansia Terlantar di Kota Tanjungpinang - Ulya Maylani Suryanti; Muhammad Incen; Nikodemus (UIN Siber Syekh Nurjati Cirebon, 2023)
Demographic changes in Indonesia indicate a significant increase in the elderly population each year, leading to the emergence of various social issues such as poverty, violent behavior, neglect, and the elderly's dependence on others. Fulfilling the daily needs of the elderly is a crucial step in enhancing their well-being, with the family playing a central role in providing support. Elderly individuals undergo significant physical, psychological, and social changes as they age, increasing their need for a place of refuge and love, particularly from their families. Therefore, this research aims to explore the role of the Social Services Department in improving the welfare of neglected elderly individuals in Tanjungpinang. The research employs a qualitative approach with a case study method. Data is gathered through interviews and documentation. Interview results are guided by interview protocols. This study identifies a range of factors that lead to elderly neglect before their admission to the Happy House Embung Fatimah, managed by the Tanjungpinang City Social Services Department. These factors encompass family issues, economic challenges, social environment concerns, and health problems. The Happy House Embung Fatimah serves as a specialized institution dedicated to caring for elderly individuals without family support. The findings of this research will provide valuable insights into efforts to enhance the well-being of neglected elderly individuals and the role of the Social Services Department in this context